2012
DOI: 10.1177/0218492312437383
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes for ischemic heart disease in dialysis-dependent patients

Abstract: Dialysis-dependent patients with ischemic heart disease have poor survival despite intervention. Coronary artery bypass achieves fewer composite adverse events and better quality of life than stenting. Symptoms and coronary anatomy should dictate treatment decisions in dialysis-dependent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…In the present study, the median survival time was 40 months, at the 95% confidence interval (28.67, 51.33). A study conducted in the U.S. reported a median survival time of 48.4 months (18), whereas another study conducted in Australia reported a median survival time of 52.3 months (25). Many studies found that a mean low serum albumin was associated with lower survival (18, 23, 26).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the median survival time was 40 months, at the 95% confidence interval (28.67, 51.33). A study conducted in the U.S. reported a median survival time of 48.4 months (18), whereas another study conducted in Australia reported a median survival time of 52.3 months (25). Many studies found that a mean low serum albumin was associated with lower survival (18, 23, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Sunagawa et al have reported that the cause of mortality in patients with DES was myocardial infarction, while with CABG it was fatal retroperitoneal bleeding, a noncardiac event. Neither Shroff nor Yeates et al have expounded on the actual cause of early mortality in the two cohorts.…”
Section: Resultsmentioning
confidence: 95%
“…). Finally, five retrospective studies (12,035 DES and 6317 CABG patients) were selected for inclusion in the systematic review. One author (P.J.E.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations